METHOD OF CONDUCT OF PRACTICAL AND LABORATORY COURSES IN PHYSICS BASED ON INTERDISCIPLINARY INTEGRATION (Neo Scientific Peer Reviewed Journal, 2024)
In the article, the model of conducting practical and laboratory training in physics based on interdisciplinary integration and the effective organization of laboratory and practical training taking into account the specific features of students' career guidance and specialization in the construction industry are considered in detail with the help of examples, and suggestions and recommendations for the effective organization of independent work are presented.